Economic Analysis of Externalities and Willingness to Accept for Waste Disposal Activities - Rima Amalia; Agus Arifin; Pahrul Fauzi (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2022)
Bantargebang integrated landfill has been assigned by Jakarta Provincial Government as a landfill for its area. The large amount of waste has a large impact and considered to have more negative impact, thus causing great losses to the local community. Jakarta Provincial Government has provided compensation but there are still complaints from residents that the compensation received has not been able to compensate all losses. This research aims to analyse the amount of compensation funds that should be received by the community and the factors that affect the community's willingness to accept, as well as to examine the impact or externalities felt by residents. The result of analysis show that the community wants a higher compensation fund than before, which is Rp497,540.98 per head of the family per month. Factors that affecting willingness to accept significantly are income, impact-specific expenses, education, type of work and distance of residence. And then there are negative externality caused by Bantargebang integrated landfill that are polluted water, piles of garbage making the air unkind to breathe and health problems. But there are also positive externality that are an increase in regional facilities and infrastructure, the creation of an increase in income and employment. Therefore, it shows the fact that people who are willing to accept compensation are greater than those who are not willing to accept compensation. It means that most people want an increase in the compensation funds they must accept from the existence of the Bantargebang Integrated Landfill. Thus, it should be a good momentum for the government to follow up through supporting actions.